Impact of pool training on balance of elderly individuals. - Andrade, Thyciane Mendonça de; Rufino, Tathiana Maria Silva; Santos, Heleodório Honorato dos; Ferreira, José Jamacy de Almeida; Clementino, Adriana Carla Costa Ribeiro; Andrade, Palloma Rodrigues de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Objective: The aim of this study was to evaluate the impact of therapeutic pool training on static and dynamic balance of sedentary elderlies. Method: 10 elderly individuals took part in the study (63.10 ± 2.33 years), and they were submitted to 24 sessions of intervention, twice a week. The assessment tools were the Balance System, Timed Up and Go Test (TUGT) and the Berg Balance System (BBS). Results: The results showed that there was a significant decrease in the global postural stability, anterior/posterior and medial/lateral scores evaluated in the dynamic platform, as well as the static global postural stability score, reduction in time to perform the TUGT and increase in the Berg Balance System score. However, no significant differences were verified in the Postural Stability tests (anterior/posterior and medial/lateral with the static platform) and in the Fall Risk. Conclusion: The regular physical training in therapeutic pool can provide sedentary elderly individuals with a significant improvement in dynamic balance.